Association between Anti-Helicobacter pylori IgG seropositivity on coronary heart disease and potential pathogenesis: a Mendelian randomization study - Jing Wang; Tianying Chang; Yiqiang Wang; Jinling Zhang; Rui Chen; Le Liu; Yingzi Cui; Hongguang Jin (PLoS ONE, 2025)
Background Currently, observational studies and clinical trials have shown that the occurrence of coronary heart disease (CHD) is closely related to anti-Helicobacter pylori (H. pylori) IgG seropositivity, but these studies may be affected by confounding factors, resulting in a causal relationship that is still controversial. Methods We conducted a Mendelian randomization analysis to clarify the association between anti-H. pylori IgG seropositivity and CHD and explore its potential pathogenesis. Exposure, outcome, and mediator data were obtained all from the genome-wide association studies (GWAS) summary data. The inverse variance weighting (IVW) analysis method under the fixed-effect model was used as our primary statistical method. Other statistical methods are supplements, such as IVW under the random-effects model, weighted median, and MR-Egger regression method. Causal estimates are presented as odds ratios (ORs) with 95% confidence intervals (CIs). To ensure the stability and reliability of the results, we also performed sensitivity and heterogeneity analysis. Results This study shows that increases of anti-H. pylori IgG seropositivity was significantly associated with an increased risk of CHD (OR=1.003, 95% CI:1.0001.006, P = 0.048) and increases in peak insulin response (β = 0.214, 95% CI: 0.025–0.403, P = 0.026), decrease in total free cholesterol levels (β = ‒0.031, 95% CI: ‒0.061 to ‒0.000, P = 0.045), decreased waist circumference (β = ‒0.073, 95% CI: ‒0.138 to ‒0.008, P = 0.027) and waist-to-hip ratio (β = ‒0.069, 95% CI: ‒0.136 to ‒0.002, P = 0.044). The leave-one-out method proved inadequate in detecting instances where a single SNP exhibited a bias towards or dependency on the causation. Furthermore, our findings revealed no heterogeneity or pleiotropy. Conclusion Our MR study provided strong evidence of a causal relationship between anti-H. pylori IgG seropositivity and related to an increased risk of CHD. The effect of anti-H. pylori IgG seropositivity on CHD may be related to a higher peak insulin response or lower total free cholesterol levels and a decrease in waist circumference and waist-to-hip ratio. However, further research is needed to prove the results.